ONTOLOGY-BASED KNOWLEDGE MODEL DESIGN FOR BALINESE GAMELAN MUSIC IN PELOG SCALE - Satyarini, Luh Made Mirah; Ariana, Anak Agung Gede Bagus; Putra, Putu Satria Udyana; Wiguna, I Komang Arya Ganda; Sarasvananda, Ida Bagus Gede (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Balinese Gamelan is an intangible cultural heritage that features complex music structures and deep cultural values. However, its preservation faces challenges like limited documentation and fragmented knowledge, which hinder efforts to preserve and educate future generations. This research aims to design and implement an ontology-based knowledge model to systematically and structurally organize information on Balinese Gamelan Music, particularly in the pelog tuning system. The study adopts the Design Science Research Methodology (DSRM), which involves five stages: problem identification, defining solution objectives, design and development, demonstration and evaluation, and communication of results. The findings indicate that the proposed ontology model consists of four main classes, 11 object properties, and 12 instances, providing a structured framework for understanding, documenting, and preserving this art form. By using semantic web technology, this ontology supports practical applications like digital repositories and educational tools, making this music more accessible and easier to understand for a wider audience.